Venous Thromboembolic Disease: The Use of “Optional” Inferior Vena Cava Filters - Venbrux, Anthony C. (Thieme Medical Publishers, 2008)
Approximately 140,000 to 200,000 patients die as a result of pulmonary embolism in the United States each year. If the diagnosis is made and therapy initiated, the mortality rate drops to 8%. Vena cava filters play a role in the management of patients with thromboembolic disease. Deployment of “optional” filters is changing practice paradigms.